President vs. Congress--does the separation of powers still work? - Daly, John Charles; Brandon, Henry; American Enterprise Institute for Public Policy Research (Washington, D.C. : The Institute, 1981)
Debate on separation of powers among the executive ,legislative,and judicial branches of the U.S government
Bibliography: p. 27.
obn25/01/2019
Loans
Keywords: Separation of powers